MODEL KERUNTUHAN PERKERASAN LENTUR - Nono Nono; Dadang AS (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Generally, the pavement design methods that are used in Indonesia are adopted from the pavement design methods from AASHTO or TRL. As we know that environment in Indonesia is different so that any model used on the pavement design methods should be adapted. This paper discussed the result of research the fatigue model for flexible pavement which is appropriate with type of pavement and environment in Indonesia. Investigate have conducted in several road link in West Java and Banten Provinces. Some conclusion from the research, are as follow: The fatigue cracking models (the asphalt mixture layer) ; Îµh = 6153,1 (N)-0,2329 The fatigue deformation models (subgrade); Îµv = 46211 (N)-0,3051 ; for ruth depth is 10 mm Îµv = 65940 (N)-0,3232 ; for ruth depth is 15 mm Îµv = 93491 (N)-0,3393 ; for ruth depth is 20 mm For three model of fatigue deformation above, should be used appropriate with road class.